TINJAUAN YURIDIS PERLINDUNGAN HUKUM HAK CUTI HAID DALAM UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Sudharma, Kadek Januarsa Adi; Artami, Ida Ayu Ketut; Rachella, Baby (Institut Hindu Dharma Negeri Denpasar, 2021)
Regulations regarding the right to menstrual leave for female workers in Indonesia are regulated in Law No. 13 of 2003 concerning Manpower. This law is the basis for the making of work agreements by every company in Indonesia, both a Fixed Time Work Agreement and an Indefinite Time Work Agreement. The work agreement is the basic principle of the relationship between workers and the company in relation to the type of work, wages, position and termination of employment. Legal protection for female workers in relation to the right to menstrual leave is implemented in article 81 paragraph (1) of Law No. 13 of 2003 concerning Manpower, usually in the form of requiring female workers to come to company clinics and have their conditions checked, if the conditions are declared unable to continue their work on that day, the female workers are given permission to rest at home. If at any time there is a dispute between workers and the company regarding menstrual leave, the dispute Resolution can be done in several ways. First, it can be resolved through negotiation by both parties or what is known as bipartite. If the bipartite settlement does not get satisfactory results for both parties, the case / dispute can be submitted to be resolved in an Industrial Relations Court.Â Keywords: Dispute Resolution, Female Workers, Legal Protection, Menstrual leave rights